2022
DOI: 10.1108/lodj-01-2022-0044
|View full text |Cite
|
Sign up to set email alerts
|

The Covid Shift: working women's punctuated equilibrium

Abstract: PurposeThe purpose of this paper is to present a conceptual framework for examining the impact of the COVID-19 pandemic on working women.Design/methodology/approachThis conceptual paper on women in the formal workforce is grounded within the leadership and organization development literature.FindingsThe authors posit the COVID-19 pandemic and the subsequent instability in the US workforce, particularly among women and mothers, is effectively examined through the lens of punctuated equilibrium. Specifically, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…The leadership landscape within and beyond higher education is shifting, so it is an opportune moment to revisit core values as a field and chart the course forward. Subsequent change is timely as the COVID‐19 pandemic spurned a renewed interest in leadership theory and practice (Purcell et al, 2022), thereby providing a pivotal moment for repositioning leadership scholarship and leadership studies at the forefront of society. Building consensus around the “new normal” is a significant moment for leadership scholars to demonstrate their expertise, relevance, and legitimacy (Butler et al, 2015; Harris & Santilli, 2021).…”
Section: Implications For Leadership Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The leadership landscape within and beyond higher education is shifting, so it is an opportune moment to revisit core values as a field and chart the course forward. Subsequent change is timely as the COVID‐19 pandemic spurned a renewed interest in leadership theory and practice (Purcell et al, 2022), thereby providing a pivotal moment for repositioning leadership scholarship and leadership studies at the forefront of society. Building consensus around the “new normal” is a significant moment for leadership scholars to demonstrate their expertise, relevance, and legitimacy (Butler et al, 2015; Harris & Santilli, 2021).…”
Section: Implications For Leadership Studiesmentioning
confidence: 99%
“…The COVID‐19 pandemic disrupted the status quo, offering a moment of punctuated equilibrium, a Covid Shift (Purcell et al, 2022), through which transformative individual, organizational, and societal growth may readily occur. Concurrently, the dual pandemic of systemic racism calls for expedited change and accountability (Hudson et al, 2022; Jones, 2021; Pradies et al, 2021).…”
Section: Implications For Leadership Studiesmentioning
confidence: 99%
“…Due to contemporary gender conventions that still see domestic chores as primarily the domain of women, working women are under great pressure to negotiate and balance their home and work obligations (Stephenson et al, 2023). Purcell et al (2022) found that gender inequality at home remains despite professional women's efforts to juggle household duties, like childcare and school runs, with full-time employment.…”
Section: Theme 3: the Impact On Childrenmentioning
confidence: 99%